“Small Tragedies of Individuals’ Lives”: London’s Migrant Division of Labour and Migrant Language Educational Settings - Zschomler, Silke (2023)
This article highlights the lived experience of migrants who have come to London to set up a new life and are learning English to facilitate this process. Drawing on my ethnographic research with a heterogenous group of adult migrants within and beyond the institutional boundaries of a migrant language educational setting in London, I tease out the often painful experiences and effects of deskilling my participants are confronted with as they are trying to make their lives in the city. Language proficiency is commonly seen as a key factor that accounts for migrants’ disparities regarding their labour market participation and linguistic competence often acts as a crucial gatekeeping mechanism to social inclusion, which is additionally impeded by wider structural constraints. In this context, my research highlights the ways in which my interlocutors find themselves caught up in entrenched forms of intersecting inequalities, unequal power relations, and the dynamics and conditions of London’s migrant division of labour. I shed light on how my participants deal with and navigate these complex processes whilst questing for the “right” linguistic competence to somehow propel their lives forward despite being aware that this might not necessarily come to fruition. I draw particular attention to the emotional cost of deskilling and being bumped down and show how this not only leaves an imprint on migrants themselves but also on those who are teaching them in order to increase migrants’ employability and social mobility.